2020
DOI: 10.18502/avr.v29i1.2368
|View full text |Cite
|
Sign up to set email alerts
|

Auditory recognition of Persian digits in presence of speech-spectrum noise and multi-talker babble: a validation study

Abstract: Background and Aim: Digits are suitable speech materials for evaluating recognition of speech-in-noise in clients with the wide range of language abilities. Farsi Auditory Recognition of Digit-in-Noise (FARDIN) test has been deve­loped and validated in learning-disabled child­ren showing dichotic listening deficit. This stu­dy was conducted for further validation of FARDIN and to survey the effects of noise type on the recognition performance in individuals with sensory-neural hearing impairment. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The study quality calculated by the PEDro checklist showed a mean score of 6.64 (standard deviation [SD]: 1.15, range: 4-8 scores). Twelve of the 14 studies were ranked as “good,” with total values of 6 to 8 [ 3 - 4 , 6 - 8 , 10 - 16 ]. The remaining two studies [ 5 , 9 ] were evaluated as “fair,” with scores between 4 and 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study quality calculated by the PEDro checklist showed a mean score of 6.64 (standard deviation [SD]: 1.15, range: 4-8 scores). Twelve of the 14 studies were ranked as “good,” with total values of 6 to 8 [ 3 - 4 , 6 - 8 , 10 - 16 ]. The remaining two studies [ 5 , 9 ] were evaluated as “fair,” with scores between 4 and 5.…”
Section: Resultsmentioning
confidence: 99%
“…The PICOS criteria of the reviewed articles are summarized in Table 3 . In most of the articles, participants consisted either of adults with normal hearing [ 3 , 7 , 9 , 12 - 13 , 15 ] or adults with hearing loss [ 3 - 6 , 14 , 16 ]. Potgieter, et al’s [ 10 ] study tested adults with both normal hearing and hearing loss.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Digit triplets also reveal very high correlation with the sentence test, despite not reflecting the general phoneme distribution of a given language [ 30 , 33 ]. In addition to the Dutch language [ 30 , 31 ], the versions of the triplet test were also prepared for Canadian English [ 34 , 35 ], Danish [ 36 ], American English [ 37 , 38 ], German [ 33 , 39 , 40 , 41 ], British English [ 42 , 43 ], Polish [ 32 ], French [ 44 ], New Zealand English [ 45 ], Swedish and Greek (unpublished, given after [ 23 ]), Finnish [ 46 ], Russian [ 47 ], Malay [ 48 ], South African English [ 24 ], Canadian French [ 35 ], Persian [ 49 ] and Korean [ 50 ]. The multiplicity of language versions indicates digit triplet test usability.…”
Section: Introductionmentioning
confidence: 99%
“…However, the adaptive optimization is feasible only if the item-specific SRT differences in normal-hearing subjects are consistent with those in hearing-impaired subjects. As the literature data on these differences are limited and ambiguous [ 38 , 49 , 53 , 54 ] more detailed studies are required. In the case of the digit triplet test, besides the digit-specific SRT, the digit position-specific SRT must also be considered.…”
Section: Introductionmentioning
confidence: 99%